The Crucial Significance of Governance, Risk and Compliance in Identity and Access Management - Eltayeb, Omer Eltayeb Omer (Journal of Ecohumanism, 2024)
This study explores the crucial part that governance, risk and compliance play in the field of identity and access management (IAM), as well as the methods for putting IAM systems into place in an efficient manner. IAM is a crucial component of modern enterprises since it supports digitization, improves security management, and ensures compliance with regulation and information security governance. However, it is normal for businesses to face significant obstacles when attempting to use IAM solutions. The emphasis in the current discussion on IAM frequently shifts from strategic considerations to operational ones, pushing the latter to the margins. Organizations are forced to deal with growing internal and external vulnerabilities and threats while also trying to stay within budgetary and resource restrictions. Strategic decision-makers, such as chief information officers and security officers, are forced by this circumstance to make thoughtful judgments about which investment programs to prioritize. IAM investments significantly impact a wide range of strategic goals, including security, agility, assurance, productivity, compliance, and empowerment. Our preliminary findings highlight the importance of compliance-driven IAM methods in contemporary businesses. Therefore, a review is conducted using PRISMA guidelines with an emphasis on the ramifications and developments in the world. The main aim of this research is to help firms implement effective IAM strategies that not only strengthen security and regulatory conformity but also match with more general strategy goals by examining the synergy between governance, risk & compliance and IAM.